ChemInform Abstract: 1‐Hydroxy‐2‐methyl‐2‐propyl Isocyanide (HMPI) as a New Convertible Isocyanide for the Ugi Four‐Component‐Coupling Reaction. Issue 7 (18th February 2014) - Oikawa, Masato; Sugamata, Yutaro; Chiba, Manami; Fukushima, Koichi; Ishikawa, Yuichi
Abstract The successful use of isocyanide (IV) in Ugi four‐component reactions is shown.